The effect of the principle of justice and the principle of good faith in providing information and Warning against the consumer in the rights of contracts - Zahra Shayesteh Majd; Jalil Ghanavati; Javad hoseinzadeh (حقوق فناوریهای نوین)
There is no doubt that the right to access information is one of the most basic rights of every buyer. This doubles the necessity of the current research in relation to the examination of contracts in this field. The leading article was written with the aim of analyzing the effect of the principle of justice and good faith on the provision of information and warnings in contract law. Therefore, the obligation to provide necessary information is one of the traditional rights of every consumer based on the principle of justice and good faith, which is certainly considered one of the duties of the strong party of the contract. This research has been compiled by content analysis method and in a library form and by referring to the regulations. The results of the research indicate that there is no definition of good faith and contractual justice in the laws of Iran. Also, the lack of strict regulations on the advertising of goods can create many problems in the direction of protection from the weak side of the contract. After conducting the research, it is concluded that in commercial dealings and providing information and warnings about contractual substitutes, it is appropriate to accept the theory of pure responsibility in Iranian law and take a big step in promoting the rights of consumers and all-round compliance. Justice in contracts should be removed.